Działalność Akcji Katolickiej w Archidiecezjach Gnieźnieńskiej i Poznańskiej (do roku 1939) - Gajowczyk, Kazimiera (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
Kazimiera Gajowczyk graduated from the Catholic Social School in Poznan and until 1939 was the director of the Office of the Catholic Action Institute in Poznan. Together with Fr. Antoni Banaszak she edited the Institute's monthly "Doniesienia" ("Reports") addressed for the parish sections of the Catholic Action. Fr. Antoni Banaszak was a meritorious activist of the Catholic Action in Poznan. After liberation from a Nazi concentration camp he lived in France and worked for the Polish Catholic Mission in Paris, up to 1982 he was rector of the Polish Seminary in Paris. He encouraged Kazimiera Gajowczyk to write the text presented here, in which she describes her experience from the activity of the Catholic Action before the Second World War. He explained his role in a letter dated 8 Dec. 1989, a photocopy of which is reproduced herewith.